Răspuns :
Răspuns:
[tex]\displaystyle {\it \dfrac{\Big( \dfrac{3}{5}\Big)^{2}}{x}=\dfrac{1}{6}+\dfrac{1}{3}+\dfrac{\dfrac{1}{4}}{\dfrac{1}{3}}-\dfrac{1}{4}}\\\\\\\it\dfrac{\dfrac{9}{25}}{x}=\dfrac{1}{6}+\dfrac{1}{3}+\dfrac{1}{4}\cdot{\dfrac{3}{1}-\dfrac{1}{4}}\\\\\\\dfrac{9}{25}\cdot\dfrac{1}{x}=\dfrac{1}{6}+\dfrac{1}{3}+ \dfrac{3}{4}-\dfrac{1}{4}}\\\\\\\dfrac{9}{25x}=\dfrac{2+4+9-3}{12}}\\\\\\\dfrac{9}{25x}=\dfrac{12}{12}}\\\\\\\dfrac{9}{25x} =1\\\\25x=9\Rightarrow \boxed{\it x=\dfrac{9}{25}} }[/tex]